Water purification and the incidence of fractures in patients receiving home haemodialysis supervised by a single centre: evidence for "safe" upper limit of aluminium in water. Issue 6422 (31st March 1984) - Platts, M M; Owen, G; Smith, S
Abstract : Between 1968 and 1980 fractures occurred in 56 of 284 patients treated by home haemodialysis in the Sheffield area for longer than one year. Patients sustained four times as many fractures while using dialysate prepared with water containing more than 1.0 mumol aluminium per 1 (2.7 micrograms/100 ml) than while using water containing a smaller concentration. When aluminium was removed from water by deionisation the incidence of fractures diminished during the next year and no patient developed dialysis encephalopathy. These findings show that 1.0 mumol/l is a safe maximum concentration of aluminium in water for use in home haemodialysis. It can be detected by the colorimetric aluminium analyses used by many water authorities. When financial resources are limited it is expedient to reserve aluminium analyses by electrothermal atomic absorption for plasma from patients receiving regular haemodialysis. Ingestion of aluminium hydroxide contributes significantly to the increased plasma aluminium concentration of these patients.